Penyuluhan Kesehatan pada Penderita Hipertensi Dewasa terhadap Tingkat Pengetahuan Hipertensi - Wulan Sulastri Marbun; Lyna M. N. Hutapea (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the effect of health education on hypertension through pre-test counseling through leaflets and post-test on increasing knowledge of hypertension sufferers. This study uses a quantitative method with a descriptive design. This study found that patients with hypertension before counseling had 69% knowledge, and after being given counseling, there was an increase in hypertension knowledge by 95%. In conclusion, there are differences in the effectiveness of counseling using leaflets on the understanding of hypertension sufferers in the work area of the Parongpong Health Center. Keywords: Hypertension, Health Counseling, Knowledge Level